2013
DOI: 10.1088/0957-4484/24/46/465301
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and fabrication of a new novel 3D injectable biosensor for high throughput genomics and proteomics in a lab-on-a-chip device

Abstract: Biosensors are used for the detection of biochemical molecules such as proteins and nucleic acids. Traditional techniques, such as Enzyme-linked Immuno-sorbent Assay (ELISA) are sensitive but require several hours to yield an assay and usually require attaching a fluorophore molecule to the target molecule. Micromachined biosensors that employ electrical detection are now being developed. Here we describe one such device, which is ultrasensitive, real time, label-free and localized. It’s called the nanoneedle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…We patterned the nanoneedle bundles by etching the 200 nm top-SiO 2 layer; 100 nm top pþ-silicon layer, and 30 nm middle oxide layer,100nmpþ-silicon layer down to bottom oxide layer. [53][54][55][56][57] We performed wet etch step to etch out the channel below the bundle of nanoneedles. Afterwards, we performed another etch step to expose the bonding pads to allow wire bonding.…”
Section: A Device Fabricationmentioning
confidence: 99%
“…We patterned the nanoneedle bundles by etching the 200 nm top-SiO 2 layer; 100 nm top pþ-silicon layer, and 30 nm middle oxide layer,100nmpþ-silicon layer down to bottom oxide layer. [53][54][55][56][57] We performed wet etch step to etch out the channel below the bundle of nanoneedles. Afterwards, we performed another etch step to expose the bonding pads to allow wire bonding.…”
Section: A Device Fabricationmentioning
confidence: 99%
“…So, it is difficult to estimate which biorecognition element to use for a given target pathogen. 19,32 There are two main biorecognition strategies: detection of viral nucleic acid (NA) sequence [32][33][34] and detection of specific viral biomolecules such as surface proteins/antigens. [35][36][37] Nanotechnology-based biosensors show high specificity and sensitivity after labeling with NA probe, antibody, or other specific molecule with affinity to the target structure.…”
Section: Biorecognition Molecules For Virus Biosensorsmentioning
confidence: 99%
“…A number of scientists consider fluorometric assays much more sensitive. 19,34 On the other hand, some recent studies focusing on the detection limit of NAEB reported analysis of NA at femtomolar 93,94 and attomolar levels. 95 The immobilization of the oligonucleotide probes on the surface of the electrode is a key step to fabricate the electrochemical oligonucleotide biosensor.…”
Section: Nucleic Acid Electrochemical Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such miniaturization can be accomplished by scaling down the optical readout instrumentation, but also by using electronic detection, which offers the added benefit of being low in cost (11). To date, several attempts at label-free electronic detection, such as detection based on impedance spectroscopy at the surface of microelectrodes (12), capacitive sensing-based approaches (13)(14)(15), and field affect transistor-based approaches (16), have been made with varying success. The main challenge with these approaches is the requirement for operation in low salt concentrations.…”
mentioning
confidence: 99%